The colors of the domes in the desert- a review - Mansour Safran, Dr. (International Journal of Engineering and Technology, 2019)
This paper mainly studies The Colors of the Domes in the desert; the mosque is for Muslims the clearest symbol of faith, a place of prayer and even in social gatherings. In Jordan, this religious building is so widespread within the large towns, small villages and in some cases the margin of the boundless desert areas. The spread of radical mosques throughout the country, from north to south of Jordan, took particular elements of recognition and visibility to differentiate the homogeneity of the constructed building that saturates the urban areas of towns and villages continues to grow. The most common type is the mosque dome, in which the interior of a quadrilateral shape is organized under a single dome in the center. This proposed approaches Methodology the dome over to play an important religious significance, as an image and symbol of the heavens and the divine transcendence, is an important visual indicator, which together enhances the looks to the minaret of the mosque. The symbolic importance of these places of worship is delayed precisely those elements required in the landscape as safe points of reference, linked to Islamic architectural tradition.
Keywords: Domes in the Desert; Muslims the Clearest Symbol; Boundless Desert Areas.